2022
DOI: 10.5194/egusphere-egu22-3844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Resolution Polar-Low Winds Obtained from Unsupervised SAR-Wind Retrieval

Abstract: <p>High-resolution sea surface observations by spaceborne synthetic aperture radar (SAR) instruments are sorely neglected resources for meteorological applications in polar regions. Such radar observations provide information about wind speed and direction based on wind-induced roughness of the sea surface. The increasing coverage of SAR observations in polar regions calls for the development of SAR-specific applications that make use of the full information content of this valuable resource. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Synthetic aperture radars (SARs) are light agnostic and provide imagery at very high spatial resolution (typically a few to tens of metres). Researchers have already indicated that SAR data adds value for monitoring polar lows [12]- [14]. Assimilation of SAR data into NWP models is however challenging, since the exact relationships between radar measurement and geophysical parameters are not trivial, especially at high wind speeds [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic aperture radars (SARs) are light agnostic and provide imagery at very high spatial resolution (typically a few to tens of metres). Researchers have already indicated that SAR data adds value for monitoring polar lows [12]- [14]. Assimilation of SAR data into NWP models is however challenging, since the exact relationships between radar measurement and geophysical parameters are not trivial, especially at high wind speeds [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have already indicated that SAR data adds value for monitoring polar lows [12]- [14]. Assimilation of SAR data into NWP models is however challenging, since the exact relationships between radar measurement and geophysical parameters are not trivial, especially at high wind speeds [14]- [16]. An alternative approach to make use of SAR data is to rely on data driven techniques, such as deep learning.…”
Section: Introductionmentioning
confidence: 99%